2005
DOI: 10.1107/s1600536805041346
|View full text |Cite
|
Sign up to set email alerts
|

5-(4-Chlorophenyl)-1-phenylpyrazolidin-3-one

Abstract: Key indicatorsSingle-crystal X-ray study T = 296 K Mean (C-C) = 0.008 Å R factor = 0.062 wR factor = 0.178 Data-to-parameter ratio = 14.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A survey of the online Cambridge Structural Database (WebCSD), in which H-bond-donor/-acceptor distances were compared, found that the average distance for 2a in five crystals of its derivatives is 0.147 Å shorter (2.703(2) vs 2.850(4) Å, see Figure a) than for 2a ′ in 12 crystal structures. Conversely, the average N···N distance in 3a derivatives in three crystal structures is 0.110 Å longer (3.013(3) vs 2.903(3), see Figure b) than 3a ′ derivatives in five crystal structures. These observations offer strong experimental support for the notion of aromaticity assisted H-bonding and aromaticity disrupted H-bonding in the cases of 2a and 3a , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A survey of the online Cambridge Structural Database (WebCSD), in which H-bond-donor/-acceptor distances were compared, found that the average distance for 2a in five crystals of its derivatives is 0.147 Å shorter (2.703(2) vs 2.850(4) Å, see Figure a) than for 2a ′ in 12 crystal structures. Conversely, the average N···N distance in 3a derivatives in three crystal structures is 0.110 Å longer (3.013(3) vs 2.903(3), see Figure b) than 3a ′ derivatives in five crystal structures. These observations offer strong experimental support for the notion of aromaticity assisted H-bonding and aromaticity disrupted H-bonding in the cases of 2a and 3a , respectively.…”
Section: Resultsmentioning
confidence: 99%